2017
DOI: 10.1016/j.neuroscience.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated retinal aging in PACAP knock-out mice

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is a neurotrophic and neuroprotective peptide. PACAP and its receptors are widely distributed in the retina. A number of reports provided evidence that PACAP is neuroprotective in retinal degenerations. The current study compared retina cell type-specific differences in young (3-4months) and aged adults (14-16months), of wild-type (WT) mice and knock-out (KO) mice lacking endogenous PACAP production during the course of aging. Histological, immunocytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 50 publications
6
30
0
Order By: Relevance
“…In our present study, we detected dramatic changes of the retinal layers after LPS-induced inflammation in the PACAP KO groups compared to the Wt ones. These findings correlated with results of other research groups, where PACAP KO mice showed increased severe retinal abnormalities in aging or ischemia [42,43].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our present study, we detected dramatic changes of the retinal layers after LPS-induced inflammation in the PACAP KO groups compared to the Wt ones. These findings correlated with results of other research groups, where PACAP KO mice showed increased severe retinal abnormalities in aging or ischemia [42,43].…”
Section: Discussionsupporting
confidence: 91%
“…PACAP KO mice had significantly greater retinal damage in ischemia compared to Wt mice [42]. Furthermore, several degenerative changes were observed at an earlier age in PACAP KO mice retina [43].…”
Section: Text: Introductionmentioning
confidence: 87%
“…Previous studies appear to support this vicious cycle hypothesis indirectly. For example, PACAP knockout mice show accelerated retinal aging (Kovács-Valasek et al, 2017). PACAP transportation across the blood brain barrier is reduced in aged mice (Nonaka et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In other aging-related neurological disorders, such as Alzheimer's disease, pre-senile systemic amyloidosis displayed an accelerated trajectory in PACAP knockout mice, supporting the concept that PACAP may serve a neuroprotective role in age-induced degenerative processes [49], likely via sequestration of β-amyloid toxicity [50]. Moreover, PACAP-knockout mice exhibit accelerated retinal aging [51]. Such aging-mediated PACAP alteration seen in mice is also observed in aged non-human primates with cognitive impairments [52], suggesting that a deficient PACAP expression pathologically manifests as learning and memory dysfunction.…”
Section: Discussionmentioning
confidence: 70%